Noli istum disturbare... Archimedes i gymnasiet - Andersen, Sebastian; Christensen, Bent; Engelund-Mikkelsen, Eva; Glunk, Claus; Højgaard, Jesper; Manly, Mathias; Strand, Hanne Eggert; Taisbak, Christian Marinus; Tortzen, Christian Gorm (AIGIS, 2024)
Intet.